A semi-automated protocol for craniometric analysis on the subadult cranial isosurface models. (December 2020) - McIntosh, Keely; Williams, Nicole; Anderson, Peter; Lottering, Nicolene
Highlights: This paper introduces a semi-automated measurement CAD protocol utilizing extreme position planes for craniometric analysis. Observer-error testing showed the protocol is highly repeatable between investigators of varying anatomical experience. Broad applications for quantification of growth in clinical and forensic practice.